2000
DOI: 10.1182/blood.v96.7.2469
|View full text |Cite
|
Sign up to set email alerts
|

The GPIb thrombin-binding site is essential for thrombin-induced platelet procoagulant activity

Abstract: The role of the platelet glycoprotein (GP) Ib-V-IX receptor in thrombin activation of platelets has remained controversial although good evidence suggests that blocking this receptor affects platelet responses to this agonist. The mechanism of expression of procoagulant activity in response to platelet agonists is also still obscure. Here, the binding site for thrombin on GPIb is shown to have a key role in the exposure of negatively charged phospholipids on the platelet surface and thrombin generation, in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(95 citation statements)
references
References 71 publications
5
86
0
4
Order By: Relevance
“…(d) Percentage surface coverage with annexin V binding platelets prior to thrombin (Control) and 10 min after the start with the thrombin/annexin V solution (þ thrombin). that SFLLRN desensitizes the thrombin-induced procoagulant response of platelets [11].…”
Section: Resultsmentioning
confidence: 94%
“…(d) Percentage surface coverage with annexin V binding platelets prior to thrombin (Control) and 10 min after the start with the thrombin/annexin V solution (þ thrombin). that SFLLRN desensitizes the thrombin-induced procoagulant response of platelets [11].…”
Section: Resultsmentioning
confidence: 94%
“…Thrombin generation initiated in platelet-rich plasma with tissue factor and Ca 21 and measured by calibrated automated thrombography has been reported to be reduced in BSS [51], and we found that P2's endogenous thrombin potential was half that of controls (data not shown) (P1 was not available for investigation). Clearly, other defects occur as a result of the reduction of GPIba that lead to the decreased prothrombin consumption/thrombin generation observed in BSS; these could include impaired binding of factor XI, thrombin and/or fibrin [51][52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin is a very potent PLT activator and binds to protease activating receptor-1 and -4 (PAR-1 and PAR-4) as well as to glycoprotein Iba. [19][20][21][22][23] TRAP-6 binds to PAR-1, but in contrast to thrombin no inhibition of fibrinogen polymerization with GPRP is required in the assay, further enhancing its feasibility.…”
Section: Discussionmentioning
confidence: 99%